Best evidence summary on positioning management in stroke patients - Xiong, Yuanfang; Pan, Mingxia; Chai, Wenting; Lei, Huijuan; Peng, Huan; Hu, Ziping; Li, Na; Liang, Yongqi; Kuang, Lingyu; Liu, Hanjiao (Frontiers in Neurology, 2025)
BackgroundStroke is the third leading cause of death in the world, characterized by high morbidity, high mortality, high disability and high recurrence rates, which brings a heavy burden to families and society. The implementation of positioning management for stroke patients can effectively improve their clinical outcomes and quality of life; however, the current evidence related to stroke is fragmented, which is not conducive to its utilization by clinical healthcare professionals.ObjectiveA systematic retrieval, critical appraisal, and synthesis of evidence on positioning management strategies for stroke patients were conducted to establish an evidence-based foundation for clinical decision-making in neurological rehabilitation.MethodsBased on the “6S” evidence resource pyramid, a top-down search strategy was employed, searching relevant databases and guideline websites, including the Scottish Intercollegiate Guidelines Network, National Institute of Health and Care Excellence, the American Heart Association, Cochrane Library, Embase, PubMed, Web of Science, CINAHL, CNKL, VIP, the Wanfang database, China Biology Medicine, UpToDate, Chinese Medical Association, the Yi Maitong Guidelines Network, Dingxiangyuan. Various types of literature such as clinical guidelines, expert consensus, systematic reviews, meta-analyses, and evidence summaries were also included. The search period covered February 2015 to February 2025. Two reviewers independently screened and critically assessed the literature, and then extracted and synthesized the evidence by grading it according to the Joanna Briggs Institute Centre for Evidence-Based Health Care Evidence Pre-grading System, Australia (2016 version).ResultsA total of 9,605 publications were retrieved, resulting in the inclusion of 12 publications, including nine clinical guidelines, one clinical decision support tool, one systematic review, and one expert consensuses. The evidence was synthesized into seven thematic areas: team composition, comprehensive assessment, head-of-bed elevation angle, body positioning Strategies, early mobilization, assistive devices, and clinical considerations. Resulting in 37 evidence-based practice recommendations.ConclusionThis study summarizes the best evidence for positional management of stroke patients, which provides an evidence-based basis for standardizing stroke positional management. However, the best evidence should be used in an individualized manner with comprehensive consideration of the actual clinical situation when the evidence is applied in order to improve the clinical outcomes and quality of life of stroke patients. In the future, it should also be combined with multi-sample and multi-center studies to validate its effect, as well as to further enrich the content of stroke position management.